Evolutionary association of receptor-wide amino acids with G protein-coupling selectivity in aminergic GPCRs - Selcuk, Berkay; Erol, Ismail; Durdag, Serdar; Adebali, Ogun (Life Science Alliance Llc, 2022)
G protein-coupled receptors (GPCRs) induce signal transduction pathways through coupling to four main subtypes of G proteins (G(s), G(i), G(q), and G(12/13)), selectively. However, G protein selective activation mechanisms and residual determinants in GPCRs have remained obscure. Herein, we performed extensive phylogenetic analysis and identified specifically conserved residues for the aminergic receptors having similar coupling profiles. By integrating our methodology of differential evolutionary conservation of G protein-specific amino acids with structural analyses, we identified specific activation networks for G(s), G(i1), G(o), and G(q). To validate that these networks could determine coupling selectivity we further analyzed G(s)-specific activation network and its association with G(s) selectivity. Through molecular dynamics simulations, we showed that previously uncharacterized Glycine at position 7x41 plays an important role in receptor activation and it may determine G(s) coupling selectivity by facilitating a larger TM6 movement. Finally, we gathered our results into a comprehensive model of G protein selectivity called sequential switches of activation describing three main molecular switches controlling GPCR activation: ligand binding, G protein selective activation mechanisms, and G protein contact.
Keywords: Crystal-Structure; Molecular-Dynamics; Complex; Gui; Recognition; Models